Driving Factors behind the Land Use Land Cover Change in Hilly Region in Gorkha Municipality, Nepal - Pokhrel, Ramjee Prasad; Kamar, Mira (The Himalayan Geographers, 2023)
Land is considered a principal source of human existence and a major type of property that has undergone changes over many years. This paper attempts to study the Land Use Land Cover (LULC) change and identify the driving factors for these changes in hilly region in Gorkha Municipality, Nepal. This study is based on spatial and attribute data acquired through both primary and secondary sources, including field studies, Google images, and topographic maps. The data was prepared using GIS tools for analysis. Key informant interviews and field observations were also conducted to assess the changes and identify the driving forces behind land use and land cover (LULC) changes from 1998 to 2020. The study reveals that LULC change is influenced by a combination of numerous driving factors, including biophysical, economic, technological, demographic, institutional, and cultural/social factors. Major driving factors of LULC change include rapid population growth, immigration, road facilities, infrastructure development, land fragmentation, expanding income dimensions, migration, deforestation, natural factors (landslides, seismic movements, and soil erosion), poor farming practices, and crops destroyed by wild animals). The study shows that the built-up area and forest area have increased while the cultivation area is decreased over the twenty two years. Hence, appropriate measures are needed to protect cultivation land to ensure sustainable conservation for human livelihood.